Action Research: Changing teachers’ attitudes towards Continuous Professional Development in a Saudi Arabian College. - Jenkins, Gavin (2017)
The purpose of the research was to investigate the beliefs, attitudes and teacher values towards Continuous Professional Development (CPD). The study introduced a bottom-up approach to CPD development where teachers identified classroom issues and then developed CPD sessions to help overcome them. Using an action research approach the participants cycled through numerous CPD sessions and discussions to create new knowledge and beliefs regarding the impact of CPD. The research found there autonomy it allowed and sense of empowerment meant teachers became more responsible and engaged with the topics. However, with the limited time the study offered there was an overwhelming classroom impact. As a result, the creation of a CPD lifecycle and mentoring program spread working alongside a bottom up CPD program could have beneficial results.